2013
DOI: 10.1364/ao.52.002454
|View full text |Cite
|
Sign up to set email alerts
|

High-power Ti:sapphire laser at 820 nm for scanning ground-based water–vapor differential absorption lidar

Abstract: The Ti:sapphire (TISA) laser transmitter of the mobile, three-dimensional-scanning water-vapor differential absorption lidar (DIAL) of the University of Hohenheim is described in detail. The dynamically-stable, unidirectional ring resonator contains a single Brewster-cut TISA crystal, which is pumped from both sides with 250 Hz using a diode-pumped frequency-doubled Nd:YAG laser. The resonator is injection seeded and actively frequency-stabilized using a phase-sensitive technique. The TISA laser is operating n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 75 publications
(111 reference statements)
0
41
0
Order By: Relevance
“…It is planned to extend the investigation of CBL characteristics in future studies also by combining the UHOH RRL data with humidity and wind observations from water vapor DIAL Wagner et al, 2013;Muppa et al, 2015) and Doppler lidar. Furthermore, also the scanning capability of the UHOH RRL will be used in the future to collect data closer to the ground and even the surface layer in order to investigate heterogeneities over different terrain.…”
Section: Discussionmentioning
confidence: 99%
“…It is planned to extend the investigation of CBL characteristics in future studies also by combining the UHOH RRL data with humidity and wind observations from water vapor DIAL Wagner et al, 2013;Muppa et al, 2015) and Doppler lidar. Furthermore, also the scanning capability of the UHOH RRL will be used in the future to collect data closer to the ground and even the surface layer in order to investigate heterogeneities over different terrain.…”
Section: Discussionmentioning
confidence: 99%
“…A temperature rotational Raman lidar (TRRL) measured temperature profiles Hammann et al, 2015;Radlach et al, 2008) and a water vapour DIAL measured absolute humidity profiles Späth et al, 2016;Wagner et al, 2013). In contrast to the Raman lidar technique, the DIAL technique, which is based on the alternating emission of laser pulses at frequencies strongly and weakly absorbed by water vapour, does not require calibration.…”
Section: Hambach Supersitementioning
confidence: 99%
“…Concerning (1), the laser transmitter is based on an injection-seeding technology. Wagner et al (2013) demonstrated that the UHOH DIAL transmitter has excellent spectral properties so that remaining systematic errors are <3 % throughout the troposphere. With respect to (2), detailed sensitivity analyses of systematic errors in the derivation of the absorption cross-section profile led to an error <1.3 % (with uncertainties of 1 K in temperature and 1 hPa in pressure, respectively) for measurements in the lower troposphere.…”
Section: The Uhoh Water Vapour Dial Systemmentioning
confidence: 99%
“…We present results obtained with recent data from our ground-based, scanning water vapour DIAL system (Wagner et al 2013). Whereas it is also possible to derive higher-order moments with water vapour Raman lidar, Wulfmeyer et al (2010) and Turner et al (2014) demonstrated that the noise level in daytime turbulence profiles is much larger than for water vapour DIAL.…”
Section: Introductionmentioning
confidence: 99%